Neutrophil Gelatinase-Associated Lipocalin (NGAL) is Associated with Symptomatic Carotid Atherosclerosis and Drives Pro-inflammatory State In Vitro. Issue 5 (May 2016) - Eilenberg, W.; Stojkovic, S.; Piechota-Polanczyk, A.; Kaun, C.; Rauscher, S.; Gröger, M.; Klinger, M.; Wojta, J.; Neumayer, C.; Huk, I.; Demyanets, S.
Abstract : Objective: Neutrophil gelatinase-associated lipocalin (NGAL), a protein found in activated neutrophils, is expressed in kidney tubule cells in response to noxious stimuli, and is thus recognized as a marker of acute kidney injury. Recent studies have suggested that NGAL could also have pathophysiological importance in cardiovascular diseases. The aim of the present study was to examine NGAL expression in human carotid endarterectomy tissues ex vivo as well as the effects of NGAL in the main cell types involved in atherogenesis, namely in human macrophages, endothelial cells, and smooth muscle cells in vitro. Methods: NGAL protein was analyzed in human endarterectomy samples from patients with asymptomatic and symptomatic carotid stenosis by immunofluorescence, and NGAL mRNA expression was detected using RealTime-PCR. Human monocyte derived macrophages (MDM), human coronary artery smooth muscle cells (HCASMC), and human umbilical vein endothelial cells (HUVEC) were treated with recombinant human (rh) NGAL at different concentrations. Interleukin (IL)-6, IL-8, and monocyte chemo-attractant protein-1 (MCP-1) were determined by specific enzyme linked immunosorbent assays (ELISAs) in culture supernatants of such treated cells. Results: Expression of NGAL protein was demonstrated by macrophages, smooth muscle cells, and endothelial cells in human carotid atherosclerotic tissue. NGAL mRNA expression was detected at a higher rate in atherosclerotic tissue of patients with symptomatic carotid stenosis (in 70%; n = 19) compared with asymptomatic patients (in 37%; n = 20, p < .001). Treatment of MDM, HCASMC, and HUVEC with rhNGAL led to a significant ( p < 0.05) and concentration dependent increase of pro-inflammatory cytokines IL-6, IL-8, and MCP-1 in all cell types analyzed. Conclusion: By induction of pro-inflammatory mediators in human macrophages, smooth muscle cells and endothelial cells, NGAL, which is predominantly expressed in atherosclerotic plaques of symptomatic patients, could be involved in creating the local and systemic pro-inflammatory environment characteristic for atherosclerosis.